2022
DOI: 10.1007/s00018-022-04163-y
|View full text |Cite
|
Sign up to set email alerts
|

N-terminome analyses underscore the prevalence of SPPL3-mediated intramembrane proteolysis among Golgi-resident enzymes and its role in Golgi enzyme secretion

Abstract: Golgi membrane proteins such as glycosyltransferases and other glycan-modifying enzymes are key to glycosylation of proteins and lipids. Secretion of soluble Golgi enzymes that are released from their membrane anchor by endoprotease activity is a wide-spread yet largely unexplored phenomenon. The intramembrane protease SPPL3 can specifically cleave select Golgi enzymes, enabling their secretion and concomitantly altering global cellular glycosylation, yet the entire range of Golgi enzymes cleaved by SPPL3 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Although this does not fully exclude binding of Frey to potential exosites on the enzyme required for substrate recruitment, these data are suggestive of a model in which Frey specifically interacts with the catalytic center of SPPL2c with high affinity, thereby blocking access of potential substrate molecules. How this high affinity can be obtained and whether an inhibitory motif within the Frey TMD might contribute to this will be a central question of further research, especially since analysis of cleavage sites of aspartic intramembrane proteases has not revealed any obvious consensus cleavage sites yet (21,23,30). Stabilization of Frey by SPPL2c represents the first described nonproteolytic function of an SPPL2c protease.…”
Section: Discussionmentioning
confidence: 99%
“…Although this does not fully exclude binding of Frey to potential exosites on the enzyme required for substrate recruitment, these data are suggestive of a model in which Frey specifically interacts with the catalytic center of SPPL2c with high affinity, thereby blocking access of potential substrate molecules. How this high affinity can be obtained and whether an inhibitory motif within the Frey TMD might contribute to this will be a central question of further research, especially since analysis of cleavage sites of aspartic intramembrane proteases has not revealed any obvious consensus cleavage sites yet (21,23,30). Stabilization of Frey by SPPL2c represents the first described nonproteolytic function of an SPPL2c protease.…”
Section: Discussionmentioning
confidence: 99%
“…S7 A ). We also tested whether the GnT-IVb smaller band is detected in the medium, because most glycosyltransferases are cleaved near the transmembrane border and secreted ( 33 ). As a result, the smaller band was not detected in the medium ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a proline mutation in a proposed hinge region in the TM domain of GNT‐V, a substrate of SPPL3, resulted in increased initial cleavage of the substrate [55]. Computational analysis of 23 SPPL3 substrates indicates a modest enrichment of glycine residues in the middle of the cleavable TM domain [118]. A recent study including deuterium exchange experiments on the APP substrate's TM domain analyzed the effect of mutations on the N‐and C‐terminal part of the substrate's TM domain as well as of a hinge region between them.…”
Section: Cleavage Mechanisms Of Aspartyl Intramembrane Proteasesmentioning
confidence: 99%
“…Sequence analysis of cleavage regions so far has not led to the identification of consensus recognition sequences within the substrate's TM domains [2,55,117]. For SPPL3, it was suggested that an M or Y in position P1 might be favorable [33]; however, a recent N-terminomics study on the enzyme did not detect a consensus sequence [118]. Yet, the authors found that when substrate and SPPL3 are located in the same compartment, the exchange of the TM domain can turn a nonsubstrate to a substrate [119].…”
Section: Initial Cleavagementioning
confidence: 99%